2015
DOI: 10.1002/dys.1493
|View full text |Cite
|
Sign up to set email alerts
|

‘It Takes Me Half a Bottle of Whisky to Get through One of Your Assignments’: Exploring One Teacher Educator's Personal Experiences of Dyslexia

Abstract: This article uses a life history approach to explore personal experiences of dyslexia of one higher education lecturer and its impact on her professional identity. The informant is currently employed as a lecturer of initial teacher training in a UK university. She worked as a primary school teacher for over a decade prior to embarking on an academic career in teacher education. The informant draws on her own experiences as a pupil, teacher and lecturer and additionally she presents accounts of student teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 30 publications
(61 reference statements)
1
16
0
15
Order By: Relevance
“…In addition to challenges arising from disability disclosure, other challenges were also noted. Glazzard and Dale (2015) found that normative teaching and learning strategies employed by able-bodied mentors and tutors produced negative attitudes and stereotyping towards student teachers with dyslexia. These normative teaching and learning strategies did not account for specialised support required by student teachers with dyslexia to foster inclusion and participation.…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition to challenges arising from disability disclosure, other challenges were also noted. Glazzard and Dale (2015) found that normative teaching and learning strategies employed by able-bodied mentors and tutors produced negative attitudes and stereotyping towards student teachers with dyslexia. These normative teaching and learning strategies did not account for specialised support required by student teachers with dyslexia to foster inclusion and participation.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Other U.K. studies indicate that structured pre-placement meetings with all practice partners and the student with a disability ensured effective communication, facilitation of reasonable accommodations and an understanding of the student's specialised needs in practice placements (Botham & Nicholson, 2014;Griffiths, 2012). For student teachers with dyslexia in their teaching practice school placements, spellcheckers, specialised software, oral communication, computers and word banks enhanced their practice learning placements (Burns & Bell, 2011;Glazzard & Dale, 2015). These best-practice models have contributed to equity arrangements for students with disabilities in practice learning placements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much rigorous research has been undertaken in the UK on the practice learning placements of SWDs. These studies highlight good practice models (Ashcroft et al 2008; Botham & Nicholson 2014; Glazzard & Dale 2015; Griffiths 2012; Griffiths, Worth, Sculliard & Gilbert 2010), stereotyping and disempowerment (Glazzard & Dale 2015) and stigma and challenges arising from disability disclosure (Botham & Nicholson 2014). Interestingly, the country’s Equality Act (2010) provides guidelines for the preparation and design of practice learning placements for SWDs, and studies suggest that such models enhance retention, access and participation.…”
Section: Literature Reviewmentioning
confidence: 96%
“…These scholars assert that prior clinical training in simulated patient care laboratories for nursing SWDs improved clinical skills and enhanced readiness and confidence for clinical practice placements. Furthermore, Glazzard and Dale (2015) and Griffiths (2012) advocate for the use of specialised technology for trainee teachers with dyslexia. Their findings show improved retention and success rates in the trainee teachers’ teaching practice school placements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such issues present challenges and occupational consequences for people with dyslexia and their families, particularly as lack of pedagogical adjustment has implications for acquisition of learning and study skills and can thus be influential on life trajectories (MacDonald, 2012), self-esteem, depression and anxiety (Glazzard & Dale, 2015). For example, up to 51% of people within the United Kingdom criminal justice system have dyslexia (MacDonald, 2012) and there is also an identified relationship between dyslexia and homelessness (MacDonald, Deacon, & Merchant, 2016).…”
Section: Introductionmentioning
confidence: 99%